Ethyl 3-ethoxy-3-iminopropanoate hydrochloride: A Versatile Precursor for Generating Next-Generation Energetic Materials - Kukreja, Sonali; Dharavath, Srinivas (Synthesis)
The construction of nitrogen-rich heterocycles is a cornerstone in developing high-energydensity materials (HEDMs). Ethyl 3-ethoxy-3-iminopropanoate hydrochloride (EEIP . HCl) has proven to be a particularly powerful precursor, offering a reliable and versatile route to make several nitrogen rich frameworks. Its ability to streamline ring formation has enabled the synthesis of high-performing energetic compounds with desirable densities, stabilities, and detonation properties. This article reviews EEIP-mediated cyclization's in energetic materials, underscoring its exceptional synthetic utility, broad structural scope, and growing role in advancing next-generation, environmentally sustainable explosives.